2006
DOI: 10.1111/j.1528-1167.2006.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

MEG Predicts Outcome Following Surgery for Intractable Epilepsy in Children with Normal or Nonfocal MRI Findings

Abstract: Summary:Purpose: To identify the predictors of postsurgical seizure freedom in children with refractory epilepsy and normal or nonfocal MRI findings.Methods: We analyzed 22 children with normal or subtle and nonfocal MRI findings, who underwent surgery for intractable epilepsy following extraoperative intracranial EEG. We compared clinical profiles, neurophysiological data (scalp EEG, magnetoencephalography (MEG) and intracranial EEG), completeness of surgical resection and pathology to postoperative seizure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 34 publications
8
84
0
4
Order By: Relevance
“…Some used geometric measures such as spike sources within 1 cm between adjacent sources (Mamelak et al, 2002;RamachandranNair et al, 2007;Almubarak et al, 2014). Some used anatomical measures such as SECDs located contiguously within neighbouring gyri (Oishi et al, 2006).…”
Section: Meg Cluster Characteristicsmentioning
confidence: 99%
“…Some used geometric measures such as spike sources within 1 cm between adjacent sources (Mamelak et al, 2002;RamachandranNair et al, 2007;Almubarak et al, 2014). Some used anatomical measures such as SECDs located contiguously within neighbouring gyri (Oishi et al, 2006).…”
Section: Meg Cluster Characteristicsmentioning
confidence: 99%
“…Several studies have shown that this method can provide reliable and useful information in presurgical patients with partial epilepsy (Stefan et al, 2003;Wu et al, 2006;RamachandranNair et al, 2007), and have concluded that non-invasive MEG techniques might eventually partly replace invasive intracranial recording techniques (Pataraia et al, 2004;Papanicolaou et al, 2005;Knowlton et al, 2006). However, the analysis procedures require that each dipole is manually reviewed and classified as either corresponding to a real spike or as corresponding to a non-epileptic origin, which can be timeconsuming, requires trained and experienced scorers, and introduces a sizeable amount of subjectivity in the results.…”
Section: Introductionmentioning
confidence: 99%
“…In children with normal or subtle nonfocal MR imaging results, MEG findings have been found to predict surgical outcome. 101 In patients with recurrent seizures following unsuccessful epilepsy surgery, MEG has a role in localizing postsurgical epileptiform disturbances, 62 because MEG is less affected by the biophysical disturbances of cranial defects and brain volume changes. One of the limitations of MEG is in identifying epileptiform paroxysms from deep-seated areas such as the mesial temporal lobe.…”
Section: Magnetoencephalographymentioning
confidence: 99%